Robust Methods for the Analysis of Income Distribution, Inequality and Poverty - Victoria-Feser, Maria-Pia (International statistical review, 2000)
Income distribution embeds a large field of research subjects in economics. It is important to study how incomes are distributed among the members of a population in order for example to determine tax policies for redistribution to decrease inequality, or to implement social policies to reduce poverty. The available data come mostly from surveys (and not censuses as it is often believed) and are often subject to long debates about their reliability because the sources of errors are numerous. Moreover the forms in which the data are available is not always as one would expect, i.e. complete and continuous (micro data) but one also can only have data in a grouped form (in income classes) and/or truncated data where a portion of the original data has been omitted from the sample or simply not recorded. Because of these data features, it is important to complement classical statistical procedures with robust ones. In this paper such methods are presented, especially for model selection, model fitting with several types of data, inequality and poverty analysis and ordering tools. The approach is based on the Influence Function (IF) developed by Hampel (1974) and further developed by Hampel, Ronchetti, Rousseeuw & Stahel (1986). It is also shown through the analysis of real UK and Tunisian data, that robust techniques can give another picture of income distribution, inequality or poverty when compared to classical ones. /// La distribution des revenus comporte une importante quantité de domaines de recherche en économie. Il est important de pouvoir étudier comment les revenus sont répartis au sein des membres d'une population pour pouvoir par exemple définir une politique de taxation et de redistribution afin de diminuer l'inégalité, ou implémenter des actions sociales pour diminuer la pauvreté. Les données à disposition proviennent essentiellement d'enquêtes (et non pas de rencensemment comme on pourrait le croire) et leur fiabilité soulève de grands débats car les sources d'erreur sont nombreuses. En plus, les données peuvent ne pas se présenter sous la forme habituelle de données continues et complètes, mais sous forme groupée (revenus par classe) et/ou sous forme censurée à savoir qu'une partie des revenus a été enlevée de l'échantillon ou simplement non enregistrée. A cause de la particularité des données, il est important de compléter les analyses statistiques classiques au moyen d'analyses robustes. Dans cet articles de telles méthodes sont présentées, spécialement pour la sélection de modèle, l'estimation de modèle avec différents types de données, l'analyse de l'inégalité et de la pauvreté, et pour les outils de comparaison de distributions. L'approache est basée sur la fonction d'influence (IF) développée par Hampel (1974) et ensuite par Hampel, Ronchetti, Rousseeuw & Stahel (1986). On montre aussi à travers l'analyse de données réelles Britanniques et Tunisiennes que les procédures robustes peuvent donner une autre représentation de la distribution des revenues, de l'inégalité et de la pauvreté lorsqu'elles sont comparées à des procédures classiques.